Symptomatology, prognosis, and clinical findings of COVID 19 induced myocarditis: a systematic review. (14th October 2021) - Jaiswal, V; Jaiswal, A; Gupta, S; Mukherjee, D
Abstract: Background: With the advent of the novel coronavirus (COVID-19) in December 2019, numerous case studies have been reported on its impact on cardiac cells, and we purpose to perform a systematic review that explains the symptomatology, prognosis, and clinical findings of COVID-19-related myocarditis patients. Methods: PRISMA guidelines were employed and peer–reviewed journals in English related to COVID – 19 were included. Exclusion criteria included <50 y, known heart problems. Age criteria was guided by prior systematic report by Kariyanna et al (2020). Search engines included Pubmed, Google scholar, Cochrane Central and Web of Science database using "SARS-CoV-2" or "COVID 19" and "myocarditis". The data were analyzed and synthesized qualitatively using MS Excel PIVOT and quality was rated using the "Research and Quality Scoring Method" by Sackett and Haynes, the Jadad scale, and the items published by Cho and Bero (Han et al., 2011). Results: A total of 22 studies on 37 patients were included; 6 were confirmed myocarditis while the rest have possible myocarditis. Among all these 62% were male and showing dominance. The most common presenting symptoms appear to be fever, chest pain, shortness of breath, and cough. Most of the patients have shown elevation in cardiac biomarkers (troponin levels, CRP, CK level, CK-MB, NT-pro BNP). Electrocardiogram changes include sinus rhythm, tachycardia, and non specific ST - segment elevation and T wave changes. Echocardiography results commonly found were left ventricular dysfunction and increased wall thickness. CMR was performed in 8 patients, with features of reduced ejection fraction, myocardial edema, and hypokinesia, whereas biopsy has been performed among 3 patients due to the invasive nature of the procedure and common findings include inflammatory biomarkers were raised. Overall Prognosis appears to be bad in which 25% of patients were not able to survive and 75% of them were recovered. Conclusions: Myocarditis-related COVID-19 mortality continues to be high and under-estimated. The patient manifestations are identical and difficult to distinguish from COVID-19-related symptoms. Just a limited number of patients undergo confirmatory tests, such as an MRI or an endomyocardial biopsy, which may not be available. Further studies are needed to confirm and quantify the actual prognosis and outcomes of patients with COVID-19 myocarditis. Moreover, available data on the usage of glucocorticoids in the coronavirus infection is controversial to our knowledge. Corticosteroid therapy is unsuccessful in the treatment of viral myocarditis, according to a Cochrane systematic review conducted in 2013. It also allows viral clearance to be overdue. Corticosteroids, on the other hand, reduce the chance of mortality for ICU patients in Wuhan. To concede, more studies, clinical trials, and duration is needed for a thorough understanding of COVID – 19, and its impact on cardiac health FUNDunding Acknowledgement: Type of funding sources: Other.